GEMPA: Game Edukasi sebagai Media Sosialisasi Mitigasi Bencana Gempa Bumi bagi Anak Autis - Rahadian Kurniawan; Affan Mahtarami; Restu Rakhmawati (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
This game was intended to provide information for children with autism on rescue procedures clearly in the form of images, simulations, and demonstrations, regarding the earthquake disaster mitigation in simple language. The game design techniques of earthquake disaster mitigation education was developed using the MDA framework. This game covers information on disaster signs, mitigation procedures, and preparing their own survival bags. The evaluation on the proposed games was conducted by examining the functionality of the game on a variety of Android devices, disaster mitigation material testing, appropriateness testing needs of children with autism, and the evaluation test understanding earthquake disaster mitigation. From the results of the evaluation of the game in two weeks, children with autism showed an increased understanding of the earthquake disaster mitigation.